Digital Health And Telemedicine In Postpartum Care: A Systematic Review Of Their Impact On Maternal Quality Of Life - Aurina Widya Hapsari; Arih Diyaning Intiasari; Dwi Sarwani (Green Publisher Indonesia, 2026)
The postpartum period is an important period characterized by various physical, psychological, social, and emotional changes that can affect the quality of life of the mother. Limited access to postpartum health services, especially in vulnerable groups and areas with limited resources, encourages the development of the use of digital health and telemedicine as an alternative to maternal health services. This study aims to identify, analyze, and synthesize scientific evidence regarding the role of digital health and telemedicine in improving the quality of life of postpartum mothers. The research uses the Systematic Literature Review (SLR) method with reference to the PRISMA guidelines. The literature search process was carried out through Google Scholar using the Publish or Perish application with the keywords